(untitled) (Fiep Bulletin - online, 2014)
This search-action was carried out in the Provisional Internment Center (CIP) of the municipality, in the period March to July 2007, seeking to understand how the practice of sports / activity physical may contribute to the construction of senses/meanings in the case respect interpersonal relationships within this institution. Thus, aimed identify sense/meanings the subject of search attached practices body during lessons for Physical Education, which examine the senses / meanings are built during the practice of physical activities and identify the contributions of the body for the practice of interpersonal relations established in the CIP (the internal / domestic; relationship internal / monitors; relationship internal / trainees). For this we open a questionnaire among the adolescents internal. Our interventions were conducted on the basis of critical-emancipatory theory proposed by Kunz (2004) allowing adolescents to participate in decision making and construction of rules adapted during lessons and discussing with them, in the initial and final assemblies, such as classroom occurred. During the speeches could understand that, first, young people are together and showed aggressive unwilling to be part of the activities proposed by us. With the passing of interventions, noticed that young people have begun to show more available for the participation of the activities and aggression between them was gradually, decreasing, and thus increasing the respect for us, we trainees. So believe in the importance of physical education to work outside the educational area school, with distinct populations such as this, because we understand that this openness allows us trainees an extension of our gaze on the practice teaching and gives the people the opportunity to socially excluded construction of other sense for their interpersonal relations and to the area of internment.